2019
DOI: 10.15540/nr.6.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Live Z-Score Neurofeedback Training for Chronic Insomnia: A Single-Case Study

Abstract: Objective/Background: Insomnia is the most common sleep disorder in the general population. Pharmacological treatments have shown efficacy in the short term, yet the symptoms return once the treatment has been withdrawn. In the search for treatment options with long-lasting effects, neurofeedback (NF) has arisen as a therapeutic option. Neurofeedback is the application of operant conditioning to brain activity. The aim of this work is to show the effectiveness of Live Z-Score NF training (LZT), a paradigm with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…No significant LZT-NF-related side effects have been reported in 15 years since the technique’s development [ 33 , 35 , 36 ]. Our previous reports [ 73 , 74 ], in several cases using the Wigton and Krigbaum method [ 38 , 39 ], and the current study further strengthen this idea.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…No significant LZT-NF-related side effects have been reported in 15 years since the technique’s development [ 33 , 35 , 36 ]. Our previous reports [ 73 , 74 ], in several cases using the Wigton and Krigbaum method [ 38 , 39 ], and the current study further strengthen this idea.…”
Section: Discussionsupporting
confidence: 85%
“…For example, Fernández et al reduced theta/alpha ratios using power training through 20 sessions [ 21 ], and Breteler et al [ 81 ] trained power and coherence through 20 sessions. However, when using LZT-NF, it has been suggested that positive clinical outcomes can be achieved within an average of 10 to 20 sessions [ 33 , 37 , 82 , 83 ], as has been reported by our group in a patient with insomnia [ 74 ]. Then another limitation might be the wide age range in this study, but we based our approach on the i-APF maturation reports [ 20 ].…”
Section: Discussionmentioning
confidence: 72%
“…The center of the normal population or the ideal instantaneous z = 0 is only a momentary ideal state in which homeostatic and balanced systems oscillate around but never achieve perfect z = 0 for the entire system. However, on average, unstable neural states that produce large • Collura et al [42] • Collura [43][44][45] • Collura [46] • Collura et al [47,48] • Decker et al [49] • Duff [50] • Frey & Koberda [51] • Foster & Thatcher [52] • Gluck & Wand [53] • Groeneveld et al [54] • Guan [55] • Hammer et al [56] • Kaur et al [57] • Keeser et al [58] • Koberda [59] • Koberda [60][61][62][63][64][65][66][67][68][69] • Koberda & Frey [70,71] • Koberda et al [71][72][73][74][75][76][77][78][79] • Krigbaum & Wigton [80] • Lambos &Williams [81] • Little et al [82] • Lubar [83] • Pérez-Elvira et al [84] • Pérez-Elvira et al…”
Section: Z-score Neurofeedback Publicationsmentioning
confidence: 99%
“…One of the approaches that has received much interest in the last decades is neurofeedback (NF) [ 3 ], a therapeutic approach based on operant conditioning applications to the electroencephalographic (EEG) activity control [ 4 ]. NF has proven to be effective in several disorders such as ADHD [ 5 , 6 , 7 ], insomnia [ 8 , 9 ], learning disabilities [ 10 , 11 ], migraine [ 12 ], depression [ 13 , 14 , 15 ], or anxiety [ 15 , 16 ]. However, for a number of subjects, the response to the NF intervention has not produced the expected results.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the effects that the value of the reinforcers on the success of NF have never been tested. Since it has been reported that positive results are achieved when the subjects choose the reinforcers with individual and personal value for them [ 9 , 10 ], the aim of the present work was to analyze whether the effects of NF on brain waves differ when reinforcers are chosen by the subject. Having this information would be a major contribution to the field of NF, since the effects of NF that are limited in some subjects could be improved by selecting a relevant stimulus according to the individuals’ expectations and preferences.…”
Section: Introductionmentioning
confidence: 99%